Effect of Different Feeding Method on Feed Conversion and Growth of Common Carp (Cyprinus carpio) in Floating Net Cage - N.B.P Utomo; P. Hasanah; I. Mokoginta (Jurnal Akuakultur Indonesia)
This experiment was conducted to evaluate the effectiveness of two feeding methods commonly used in cage culture of carp Cyprinus carpio at Jatiluhur Lake. The results showed that the application of "at satiation feeding method" was more effective than "fixed method" (8% of body weight) indicating with food conversion ratio of 1.79 versus 1.84 and daily growth rate of 3.79% versus 3.42%.